Co‐Assembly of Colloids and Eumelanin Nanoparticles in Droplets for Structural Pigments with High Saturation. Issue 7 (3rd December 2021) - Han, Sang Hoon; Choi, Ye Hun; Kim, Shin‐Hyun
Abstract: Colloidal crystals have been used to develop structural colors. However, incoherent scattering causes the colors to turn whitish, reducing the color saturation. To overcome the problem, light‐absorbing additives have been incorporated. Although various additives have been used, most of them are not compatible with a direct co‐assembly with common colloids in aqueous suspensions. Here, the authors suggest eumelanin nanoparticles as a new additive to enhance the color chroma. Eumelanin nanoparticles are synthesized to have diameters of several nanometers by oxidative polymerization of precursors in basic solutions. The nanoparticles carry negative charges and do not weaken the electrostatic repulsion among same‐charged polystyrene particles when they are added to aqueous suspensions. To prove the effectiveness of eumelanin as a saturation enhancer, the authors produce photonic balls through direct co‐assembly of polystyrene and eumelanin using water‐in‐oil emulsion droplets, while varying the weight ratio of eumelanin to polystyrene. The high crystallinity of colloidal crystals is preserved for the ratio up to at least 1/50 as the eumelanin does not perturb the crystallization. The eumelanin effectively suppresses incoherent scattering while maintaining the strength of structural resonance at an optimum ratio, improving color chroma without compromising brightness. Abstract : Eumelanin nanoparticles are synthesized as novel additives of color‐saturation enhancers for colloidal crystals. As the eumelanin nanoparticles are sufficiently small and negatively charged, they are highly compatible with the self‐assembly of common water‐borne colloids with the same charge. The nanoparticles co‐assembled with latex particles effectively suppresses incoherent scattering while maintaining the strength of structural resonance, improving color chroma.